Kecemburuan sebagai Moderator pada Kualitas Hubungan Romantis dan Kesejahteraan Subjektif Dewasa Awal Berstatus Menikah - Karina Tria Meliani; MIF Baihaqi; Anastasia Wulandari (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to examine the effect of romantic relationship quality on subjective well-being moderated by jealousy on married adolescents. This study used quantitative method with the participants were 300 married adolescents aged 21 to 30 years old in Bandung. The sampling technique used nonprobability sampling that is accidental sampling. The instrument used adaptation of Scale of Positive and Negative Experience (SPANE), The Satisfaction with Life Scale (SWLS), The Perceived Relationship Quality Component (PRQC), and The Interpersonal Jealousy Scale. The data analysis used simple and multiple regression. The results show that jealousy variable can statistically and significantly moderate the effect of romantic relationship quality on subjective well-being. The regression results of jealousy on different groups, that is high, medium, and low, lead to different results on its effect on subjective well-being.